Developing deprivation measures for Northern Ireland - Noble, Michael; Lloyd, Myfanwy; Wright, Gemma; Dibben, Chris; Smith, George (Statistical and Social Inquiry Society of Ireland, 2002)
This paper outlines the development of a measure of ?multiple deprivation? for Northern Ireland at small area level. To best construct such a measure, it is essential to have a clear conceptual model and translate this into a series of measures using the best data at hand. Thus, each dimension is measured independently using the best indicators available to generate a score or domain measure for each aspect of deprivation. These domain scores are then combined, with explicit weighting, to generate a multiple deprivation measure which is an aggregate of the component domains. The availability of new data has allowed these domains to be described with more precision, and in a more robust and consistent way than has been possible before. It is the hope of the researchers that as data quality and sources improve, so will the estimation procedures, as the multiple deprivation measure is reviewed and developed over time.
Read before the Society, 27 September 2001
Keywords: Multiple deprivation; Domain score; Poverty; 314.15